Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.11.06.370676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent SARS-CoV-2 neutralizing antibodies selected from a human antibody library constructed decades ago

Abstract: Combinatorial antibody libraries not only effectively reduce antibody discovery to a numbers game, but enable documentation of the history of antibody responses in an individual. The SARS-CoV-2 pandemic has prompted a wider application of this technology to meet the public health challenge of pandemic threats in the modern era. Herein, we used a combinatorial human antibody library constructed 20 years before the COVID-19 pandemic to discover three highly potent antibodies that selectively bind SARS-CoV-2 spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
(82 reference statements)
2
6
0
Order By: Relevance
“…3d ). This is consistent with previous findings of affinity maturation, which normally occurs after the second exposure to the pathogen 3133 , and is further supported by the finding that many SARS-CoV-2 antibodies have germline sequences without hyper-affinity maturation in germinal centres 3436 .…”
Section: Resultssupporting
confidence: 93%
“…3d ). This is consistent with previous findings of affinity maturation, which normally occurs after the second exposure to the pathogen 3133 , and is further supported by the finding that many SARS-CoV-2 antibodies have germline sequences without hyper-affinity maturation in germinal centres 3436 .…”
Section: Resultssupporting
confidence: 93%
“…The low-affinity antibodies or poorly neutralizing antibodies which might be produced after vaccine injection should also be considered during vaccine design. Other efforts to diminish ADE is to introduce LALA mutation in the Fc part of IgG1 ( Renn et al, 2020 ) or adopt the IgG4 format ( Qiang et al, 2020 ) for neutralizing antibodies development. Nanobodies or antibodies in Fab format with no Fc part have the natural advantage of avoiding ADE.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Antibody library in various types such as single chain (scFv) antibody library, single domain antibody library, Fab antibody library, etc. were employed for selection ( Qiang et al, 2020 , Wang et al, 2020 ) when competition screen with ACE2 was a common selection strategy adopted ( Zeng et al, 2020 ).…”
Section: Pharmaceutical Antibodies Developed By Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is the biggest global health threat in many generations. Recently it has been reported that a combinatorial human antibody library, constructed 20 years before the current COVID-19 pandemic, was used to select three highly potent antibodies that specifically bind the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein, and neutralize authentic SARS-CoV-2 virus [ 67 ]. This suggests that immunological memory after infection with seasonal human coronaviruses may potentially contribute to cross-protection against SARS-CoV-2 [ 68 , 69 ].…”
Section: Antibody Libraries and Emerging Viral Infectionsmentioning
confidence: 99%